The effects of birth order on personality traits and feelings of academic sibling rivalry - Badger, JR; Reddy, P (British Psychological Society, 2009)
The influence of birth order on personality and sibling rivalry is controversial; little research has been conducted into academic sibling rivalry, and none into the connection with personality traits. This study considers the interaction of all three factors. Firstborns (N=22) and lastborns (N=24) completed online personality tests and an Academic Sibling Rivalry Questionnaire. Lastborns were found to experience more academic sibling rivalry: t=2.33, DF=44; p<.05, whereas firstborns are more likely to be conscientious: F(1,44)=3.58; p< .05, and dutiful: F(1,44)=5.39; p<.05. This raises possible implications in domains including education, health and psychotherapy. Further research could be conducted to expand these findings in terms of variables and geographical location.